Answer:
[tex]4x^5\sqrt[3]{3x}[/tex]
Step-by-step explanation:
The product will be written as:
[tex]\sqrt[3]{16x^7}*\sqrt[3]{12x^9}[/tex]
As both the radicals have same root 3 so,
[tex]= \sqrt[3]{16x^7 * 12x^9}[/tex]
The powers of x will be added as the base is same
[tex]=\sqrt[3]{16*12 * x^{(7+9)}}\\=\sqrt[3]{192x^{16}}\\[/tex]
We have to break the terms so that the powers can be written as a multiple of 3
[tex]=\sqrt[3]{64*3*x^{15}*x}\\ =\sqrt[3]{(4^3)*3*(x^{3*5})*x}\\ Applying\ cube\ root\\= 4x^5\sqrt[3]{3x}[/tex]
What is the exact value of sin 112.5
Answer:
The fourth one: [tex]\frac{\sqrt{2+\sqrt{2} } }{2}[/tex]
Step-by-step explanation:
The exact value of sin 112.5° can be found using the half-angle identity formula. Substituting values for sin 45° and cos 90°, we find that the exact value of sin 112.5° is ± √2/2.
Explanation:We can find the exact value of sin 112.5 using half-angle identity. As we know, 112.5 degrees is equal to 45 degrees/2 + 90 degrees, these values are much simpler to work with. Let's start by understanding the half-angle formula, which is sin(x/2) = ± √[(1 - cos x) / 2] .
The exact value of sin 45 degrees is √2/2 and cos 90 degrees is 0.
Now, let's put these values in our half-angle formula
sin 112.5 = sin(45/2 + 90) = √[(1 - 0) / 2] = ± √[1/2] = ± √2/2
Learn more about sin 112.5 here:https://brainly.com/question/34962518
#SPJ11
27a⁰c³ for a =⅔, c = -⅓
need answer and if you could explain how to solve problem that would be much appreciated.
Answer:
- 1
Step-by-step explanation:
Using the rules of exponents
[tex]a^{0}[/tex] = 1
[tex](a^n)^{m}[/tex] = [tex]a^{nm}[/tex]
Given
27[tex]a^{0}[/tex][tex](-\frac{1}{3}) ^{3}[/tex]
Note [tex]a^{0}[/tex] = 1 for any value of a, thus
= 27 × 1 × - [tex]\frac{1}{3^{3} }[/tex]
= 27 × 1 × - [tex]\frac{1}{27}[/tex] ← cancel the 27 on numerator/ denominator
= 1 × - 1
= - 1
what equation describes the same line as y-5 =-2(x+4)
Answer:
y = - 2x - 3
Step-by-step explanation:
Given
y - 5 = - 2(x + 4) ← in point- slope form
Distribute the right side
y - 5 = - 2x - 8 ( add 5 to both sides )
y = - 2x - 3 ← in slope- intercept form
what is the solution of this equation
w+9=14
Answer:
w=5
Step-by-step explanation:
14-9=5
[tex]\huge\text{Hey there!}[/tex]
[tex]\huge\text{ w + 9 = 14}[/tex]
[tex]\huge\text{SUBTRACT by the \#9 on your sides! }[/tex]
[tex]\huge\text{Like: w + 9 - 9 = 14 - 9}[/tex]
[tex]\huge\text{Cancel out: 9 - 9 because it equals 0}[/tex]
[tex]\huge\text{Keep: 14 - 9 because it helps us solve for w}[/tex]
[tex]\huge\text{w = 14 - 9}[/tex]
[tex]\huge\text{14 - 9 = w}[/tex]
[tex]\huge\text{14 - 9 = 5}[/tex]
[tex]\huge\text{w = 5}[/tex]
[tex]\boxed{\boxed{\huge\text{Answer: w = 5}}}\huge\checkmark[/tex]
[tex]\text{Good luck on your assignment and enjoy your day!}[/tex]
~[tex]\frak{LoveYourselfFirst:)}[/tex]
A new dolphin tank is being built outside of Houston. The tank will be a cylinder with a depth of 42 feet and a radius of 240 feet. How many cubic feet of water will the tank hold? Use π = 3.14
A. 30,400,564 ft³
B. 7,596,288 ft³
C. 31,667 ft³
D. 3,237,000 ft³
Answer:
B. 7,596,288 ft³
Step-by-step explanation:
volume of cylinder = π * r^2 * h
volume = 3.14 * (240 ft)^2 * 42 ft
volume = 7,596,288 ft³
Answer: B . [tex]7,596,288 ft^3[/tex]
Step-by-step explanation:
The volume of a cylinder is given by :_
[tex]\text{Volume}=\pi r^2 h[/tex], where r is radius and h is height of the cylinder.
Given : A new dolphin tank is being built outside of Houston. The tank will be a cylinder with a depth of 42 feet and a radius of 240 feet.
i.e. r=240 and h = 42
Now, the volume of tank will be :_
[tex]\text{Volume}=(3.14) (240)^2 (42)=7,596,288[/tex]
Hence, the tank will hold [tex]7,596,288 ft^3[/tex] water.
A watch company is developing packaging for its new watch. The designer uses hexagons with a base area of 25 in squared and rectangles with a length of 10 in to create a prototype for the new package. What is the volume of the prototype?
How do I set this up?
Answer:
The volume of the prototype is [tex]V=250\ in^{3}[/tex]
Step-by-step explanation:
we know that
The volume of a hexagonal prism is equal to
[tex]V=BH[/tex]
where
B is the area of the hexagonal base
H is the length of the rectangular face
we have
[tex]B=25\ in^{2}[/tex]
[tex]H=10\ in[/tex]
substitute
[tex]V=(25)(10)[/tex]
[tex]V=250\ in^{3}[/tex]
Answer:
Volume of the prototype is 250 in.³
Step-by-step explanation:
Given:
Base area of the watch packaging case = 25 in.²
Length of the rectangle on the side = 10 in.
To find: Volume of the packaging prototype.
Prototype of the packaging of the watch is in shape of prism whose base is a hexagon and sides are in shape of rectangle.
So, Volume of the prism = Base Area × Height
Thus, Volume of the Prototype = 25 × 10
= 250 in.³
Therefore, Volume of the prototype is 250 in.³
Solve for x: 2/5 (x − 2) = 4x. (1 point) I don't understand what to do for this problem. Can someone help??
Answer:
-2/9 =x
Step-by-step explanation:
2/5 (x − 2) = 4x
Multiply each side by 5/2
I do this because we want to get rid of the fraction in the denominator. I also know that the right side has a 4 in the numerator so, the 2 in the denominator that we are multiplying by will cancel.
5/2 *2/5 (x − 2) = 4x*5/2
x-2 = 20/2 x
x-2 = 10x
Subtract x from each side
x-2 -x = 10 -x
-2 = 9x
Divide each side by 9
-2/9 =9x/9
-2/9 =x
Answer:
x=-2/9
Step-by-step explanation:
First, divide both sides by 2/5
(2/5)*(x-2)/2/5=4x*5/2
x-2=10x, Subtract x from both sides.
-2=9x, Divide both sides by 9
x=-2/9, If you need you can check your answer by substituting the value of x into the original equation.
How do you find the base area of a rectangular prism and a cylinder? Please help
Answer:
See explanation.
Step-by-step explanation:
The 'base' of a rectangular prism refers to only one side of the rectangular prism, which is a rectangle.
The formula for the area of a rectangle is as follows:
[tex]A=lw[/tex]
Where A = area, l = length, and w = width.
The 'base' of a cylinder refers to only one side of the cylinder, which is a circle.
The formula for the area of a circle is as follows:
[tex]A=\pi r^2[/tex]
Where A = area and r = radius.
Just in case you typed your question incorrectly and were asking for surface area, here is the formula for surface area for both as well:
Rectangular prism: [tex]A=2(wl+hl+hw)\\[/tex]
Cylinder: [tex]A=2\pi rh+2\pi r^{2}[/tex]
which logic statement represents this argument? If it’s a weekend, I exercise. It’s not a weekend. So, I won’t exercise. Assume that p represents it’s a weekend and q represents “I exercise.”
28 points!!
Answer:
p->q.
~p.
[tex]\therefore[/tex] ~q.
Step-by-step explanation:
I'm going to assume you are looking for symbolic representation.
p=it's a weekend
q=I exercise
The arrangement is this:
If it’s a weekend, I exercise. It’s not a weekend. So, I won’t exercise.
If p , q . ~p . So, ~q.
I try to space out my symbols to show you what I was replacing with what. (By the way I'm still not done.)
I replaced "it's a weekend" with p.
I replaced "it's not a weekend" with ~p which means not p.
I replaced "I exercise" with q.
I replaced 'I won't exercise" with ~q which means not q.
If then, statements are symbolized with an arrow, ->. Example, p->q means if p then q.
Back to the argument:
If it’s a weekend, I exercise. It’s not a weekend. So, I won’t exercise.
If p , q . ~p . So, ~q.
This first sentence is an if then statement with hypothesis p and conclusion q so it can be rewritten as p->q.
I'm going to replace so with [tex]\therefore[/tex]. I'm just trying to show what the conclusion of the argument is with this symbol.
This is the argument in symbolic representation:
p->q.
~p.
[tex]\therefore[/tex] ~q.
This is translated into English as "If it's a weekend, I exercise" (p q), "It's not a weekend" (p), and "I won't exercise" (q).
What exactly is a logic statement?A logic statement is a statement that uses logical symbols and operators to represent the relationships between propositions or statements.
It is a formal expression of symbolic logic that can be evaluated as true or false based on the truth values of its constituents.
Logic statements are used to reason about the truth of statements and the validity of arguments in mathematics, philosophy, computer science, and other fields.
"If p then q," "p and q," "p or q," "not p," and "p if and only if q" are all logical statements.
The logic statement that represents this argument is:
(p → q) ∧ ¬p → ¬q
Thus, when translated into English, this reads: "If it's a weekend, I exercise" (p → q), "It's not a weekend" (¬p), therefore "I won't exercise" (¬q).
For more details regarding logical statement, visit:
brainly.com/question/4458769
#SPJ7
Your question seems incomplete, the probable complete question is:
Which logic statement represents this argument? If it’s a weekend, I exercise. It’s not a weekend. So, I won’t exercise. Assume that p represents “It’s a weekend” and q represents “I exercise.” (p q) p [(p q) p] q [(p q) p] q [(p q) p] q
Myra owns a car service that charges a $5 flat rate and an additional $0.50 per mile, which is represented by the equation y = 0.5x + 5, where x is the number of miles and y is the total cost.
How much is the total cost for a car with 30 miles?
$10
$15
$20
$35
Answer:
Option C is correct.
Step-by-step explanation:
The equation given is y = 0.5x +5
where x is the number of miles and y is the total cost.
We need to find total cost y if the car has traveled 30 miles
so, x=30
Putting value of x in the given equation:
y = 0.5x +5
y = 0.5(30) + 5
y = 15 + 5
y = 20
So, the total cost is $20
Option C is correct.
Answer:
the answer is $20 i just did that one :))
Step-by-step explanation:
good luck!
Find the equation of the ellipse with the following properties.
The ellipse with x-intercepts (5, 0) and (-5, 0); y-intercepts (0, 3) and (0, -3).
Check the picture below.
[tex]\bf \textit{ellipse, horizontal major axis} \\\\ \cfrac{(x- h)^2}{ a^2}+\cfrac{(y- k)^2}{ b^2}=1 \qquad \begin{cases} center\ ( h, k)\\ vertices\ ( h\pm a, k)\\ c=\textit{distance from}\\ \qquad \textit{center to foci}\\ \qquad \sqrt{ a ^2- b ^2} \end{cases} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \begin{cases} h=0\\ k=0\\ a=5\\ b=3 \end{cases}\implies \cfrac{(x-0)^2}{5^2}+\cfrac{(y-0)^2}{3^2}=1\implies \cfrac{x^2}{25}+\cfrac{y^2}{9}=1[/tex]
What was done to the quadratic parent function F(x) = xto get the
function G(X) = x2 - 3? 0
A.Shifted 3 units to the right
B. Vertically stretched by multiplying by 3
C.Shifted 3 units down
D.Shifted 3 units to the left
Answer:
Step-by-step explanation:
Given the function f(x), the function g(x) = f(x) + k represents the function f(x) shifted k units downwards.
In this case, given that k=-3 (k<0). The graph is shifted 3 units down. Therefore, we can conclude that the correct option is Option C.
A pizza shop sells pizzas that are 10 inches (in diameter) or larger. A 10-inch cheese pizza costs
$8. Each additional inch costs $1.50, and each additional topping costs $0.75. Write an equation
that represents the cost of a pizza. Be sure to specify what the variables represent
Answer: [tex]T=8+ 1.50 x+0.75y[/tex] , where 'x' denotes the number of additional inch to the pizza and 'y' denotes the number of additional toppings.
Step-by-step explanation:
Let 'x' denotes the number of additional inch to the pizza and 'y' denotes the number of additional toppings.
Given : A 10-inch cheese pizza costs $8.
i.e. Fixed cost = $8
Each additional inch costs $1.50, and each additional topping costs $0.75.
∴ Cost of additional inch = $1.50 x
∴ Cost of additional topping = $0.75y
Then The Total cost of any pizza would be :
Total cost = Fixed cost + Cost of additional inch + cost of additional topping
= $8+ $1.50 x+$0.75y
⇒ Equation that represents the cost of a pizza :
[tex]T=8+ 1.50 x+0.75y[/tex]
An equation that represents the cost of a pizza will be C = 8 + 1.50x + 0.75y
Fixed cost = $8Cost of additional inch = 1.50xCost of additional topping = 0.75y
Total cost (C) will then be:
= 8 + (1.50 × x) + (0.75 × y)
C = 8 + 1.50x + 0.75y
Therefore, the equation to represent the cost is C = 8 + 1.50x + 0.75y
Read related link on:
https://brainly.com/question/12336191
If the quadratic formula is used to find the solution set of 3x2 + 4x - 2 = 0, what are the solutions?
Answer:
[tex]x=\frac{-2}{3} \pm \frac{\sqrt{10}}{3}[/tex]
Step-by-step explanation:
Compare [tex]ax^2+bx+c[/tex] to [tex]3x^2+4x-2[/tex].
We have [tex]a=3,b=4,c=-2[/tex].
The quadratic formula is for solving equations of the form [tex]ax^2+bx+c=0[/tex] and is [tex]x=\frac{-b \pm \sqrt{b^2-4ac}}{2a}[/tex].
So we are going to plug in our values in that formula to find our solutions,x.
If you want to notice it in parts you can.
Example I might break it into these parts and then put it in:
Part 1: Evaluate [tex]b^2-4ac[/tex]
Part 2: Evaluate [tex]-b[/tex]
Part 3: Evaluate [tex]2a[/tex]
------Let's do these parts.
Part 1: [tex]b^2-4ac=(4)^2-4(3)(-2)=16-12(-2)=16+24=40[/tex].
This part 1 is important in determining the kinds of solutions you have. It is called the discriminant. If it is positive, you have two real solutions. If it is negative, you have no real solutions (both of the solutions are complex). If it is 0, you have one real solution.
Part 2: [tex]-b=-4[/tex] since [tex]b=4[/tex].
Part 3: [tex]2a=2(3)=6[/tex].
Let's plug this in:
[tex]x=\frac{-b \pm \sqrt{b^2-4ac}}{2a}[/tex]
or in terms of our parts:
[tex]x=\frac{\text{Part 2} \pm \sqrt{\text{Part 1}}}{\text{Part 3}}[/tex]
[tex]x=\frac{-4 \pm \sqrt{40}}{6}[/tex]
40 itself is not a perfect square but it does contain a factor that is. That factor is 4.
So we are going to rewrite 40 as [tex]4 \cdot 10[/tex].
[tex]x=\frac{-4 \pm \sqrt{4 \cdot 10}}{6}[/tex]
[tex]x=\frac{-4 \pm \sqrt{4} \cdot \sqrt{10}}{6}[/tex]
[tex]x=\frac{-4 \pm 2\cdot \sqrt{10}}{6}[/tex]
I'm going to go ahead and separate the fraction like so:
[tex]x=\frac{-4}{6} \pm \frac{2 \cdot \sqrt{10}}{6}[/tex]
Now I'm going to reduce both fractions:
[tex]x=\frac{-2}{3} \pm \frac{1 \cdot \sqrt{10}}{3}[/tex]
[tex]x=\frac{-2}{3} \pm \frac{\sqrt{10}}{3}[/tex]
Final answer:
Using the quadratic formula with a=3, b=4, and c=-2, the solution set for the quadratic equation 3x^2 + 4x - 2 = 0 is x = (-4 + 2√(10)) / 6 and x = (-4 - 2√(10)) / 6.
Explanation:
To find the solution set of the quadratic equation 3x2 + 4x - 2 = 0, we can use the quadratic formula:
x = (-b ± √(b2 - 4ac)) / (2a)
Here, comparing with the standard form ax2 + bx + c = 0, we identify a = 3, b = 4, and c = -2. Substituting these values into the quadratic formula gives us:
x = (-(4) ± √((4)2 - 4(3)(-2))) / (2(3))
x = (-4 ± √(16 + 24)) / 6
x = (-4 ± √(40)) / 6
x = (-4 ± 2√(10)) / 6
Which simplifies to two solutions:
x = (-4 + 2√(10)) / 6
x = (-4 - 2√(10)) / 6
These are the two solutions to the given quadratic equation.
Determine if the two expressions are equivalent and explain your reasoning. show all work plzs
11p + 2(p + 3) and 1 + p(13) + 2
Answer:
Not equivalent.
Step-by-step explanation:
Simplifying the first expression:
11p + 2(p + 3) Distribute the + 2 over the parentheses:
= 11p + 2p + 6
= 13p + 6. **
Now, the second:
1 + p(13) + 2
= 13p + 1 + 2
= 13p + 3. **
So they are not equivalent.
???? I’m very confused
If f(x) = x/1 + x, what is the value of f(x+h)
Answer:
[tex]f(x+h)=\frac{x+h}{1+x+h}[/tex]
Step-by-step explanation:
Given function is:
f(x) = x/1 + x
In order to find f(x+h) we have to put x+h in place of x
[tex]f(x)=\frac{x}{1+x} \\f(x+h)=\frac{x+h}{1+x+h}[/tex]
Therefore,
[tex]f(x+h)=\frac{x+h}{1+x+h}[/tex]
Answer: B
Got it right lol
Simplify 6 / (7+3i).
Answer:
To simplify the following expression: 6 / (7+3i), we're going to multiply and divide the entire expression by (7+3i), as follows:
[tex]\frac{6 (7-3i)}{ (7+3i)(7-3i)} = \frac{42-18i}{58} = 0.72 - 0.31i[/tex]
Now, the denominator has NO imaginary numbers.
Answer:
21/29 - 9/29i
f(x) = 3x^4 is even or odd?
Answer:
Step-by-step explanation:
it's even because f(-x)=f(x)
Answer:
even function
Step-by-step explanation:
recall that:
a function is EVEN if and only if f(-x) = f(x) for all x in the domain of f
a function is ODD if and only if f(-x) = -f(x) for all x in the domain of f
we observe that for the function
f(x) = 3x^4
because x has been raised to an even power, that f(x) will always be positive (or zero), regardless of whether x is negative or positive.
i.e
f(x) = f(x) and f(-x) = f(x)
This behavior is described by the definition of an EVEN function (given above)
Hence f(x) is an even function
To which subsets of the real numbers does 2 radical 2 belong?
(a) Natural
b) Whole
c) Irrational
d) Integers
e) Rational
Answer:
[tex]2\sqrt{2}[/tex] is irrational .
Step-by-step explanation:
The Natural numbers are {1,2,3,4,5,6,7,....}.
Natural numbers are also called counting numbers because they are numbers people use to count with.
Whole numbers are almost the same as natural numbers. They include one extra number which is 0.
So the whole numbers are {0,1,2,3,4,5,6,7,...}.
Irrational numbers are real numbers that aren't rational numbers.
Rational numbers are number that can be written as fractions where the numerator and denominator are integers (bottom integer is not 0).
Terminating decimals, repeating decimals, and integers all can be written this way which makes them rational.
Integers are numbers in the set {...,-4,-3,-2,-1,0,1,2,3,4,...}. So these are your counting numbers, 0, and the opposite of your counting numbers.
You want to figure out which set does [tex]2\sqrt{2}[/tex] belong to.
You cannot simplify this number anymore than it is. So this is definitely not a number you can count to. It is not the opposite of a counting number. It is also not 0. We have ruled out the following sets: Natural, whole, and integers.
So it is between rational and irrational.
[tex]\sqrt{a} \text{ is irrational if } a \text{ is not a perfect square}[/tex].
[tex]\sqrt{a} \text{ is rational if } a \text{ is a perfect square}[/tex].
2 is not a perfect square.
[tex]\sqrt{2} \text{ is irrational}[/tex]
So [tex]2\sqrt{2} \text{ is also irrational}[/tex]
Select one answer for part A and one answer for part B
what is the slope of the line shown below? (5, 11) (-5, -1)
Answer:
-6/-5 is the slope
Step-by-step explanation:
Y2 - Y1 / X2 - X1 so
-1 - 11 / -5 - 5 = -12 / -10 simply it and get -6 / -5
Slope equals rise over run
Answer:
6/5
Step-by-step explanation:
The shapes of the horizontal cross-sections of the cone below are all congruent
except for the vertex.
True or False
Answer: false
Step-by-step explanation:
The statement that the shapes of the horizontal cross-sections of the cone below are all congruent except for the vertex is false
The horizontal cross-sections of a cone contains a circle, while the vertical cross-sections contains a triangle
The triangle and the cone may or may not have the same area.
Hence, the statement is false
Read more about horizontal cross-sections at:
https://brainly.com/question/11827
Solve for x 2 + 2 * x = 10
Answer:
6
Step by step explanation:
2 + 2 * x = 10
2x+2=10
2x+2−2=10−2
Therefore, x = 6
Write the Explicit Rule for the arithmetic sequence:
Qp = Q1 +(n-1)d
8, 5, 2, -1, ...
Answer:
Last choice.
Step-by-step explanation:
8, 5, 2, -1, ...
Make a table
n | 1 2 3 4 5
an | 8 5 2 -1 -4
You really should just think of this as finding the equation of a line.
The slope can be used by using any two points.
How about
(1 , 8) and
(2 , 5)?
------------I really like to find the slope by lining up my points and subtracting vertically and then putting second number on top of first.
That is the same as using the formula directly which is (y2-y1)/(x2-x1)
or (y1-y2)/(x1-x2) which gives you the same thing too.
Subtracting the pairs now:
(1 , 8)
-(2 , 5)
-----------
-1 3
So the slope is 3/-1 or -3/1 or -3.
So you can already rule out choice B.
So we have the equation is y=-3x+b
where y really represents an and x really represents n here.
You can use any point that you know is on the line to find b.
How about (1,8)?
Plug it into y=-3x+b.
y=-3x+b
8=-3(1)+b
8=-3+b
11=b
So the line is y=-3x+11
Want to confirm?
No problem:
At x=1 you have y=-3(1)+11=-3+11=8 which is first number in the list.
At x=2 you have y=-3(2)+11=-6+11=5 which is second number in the list.
At x=3 you have y=-3(3)+11=-9+11=2 which is the third number in the list.
At x=4 you have y=-3(4)+11=-12+11=-1 which is the fourth number in the list.
So we have confirmed our solution of y=-3x+11.
So the answer is an=-3n+11
Using the linear combaination method what is the solution to the system of linear equations 7x-2y=-20and9x+4y=-6
Answer:
x=-2 y=3
Step-by-step explanation:
7x-2y=-20
9x+4y=-6
Multiply the first equation by 2
2(7x-2y) = 2 * -20
14x - 4y = -20
Add this to the second equation
14x - 4y = -40
9x+4y=-6
--------------------------
23x = -46
Divide by 23
23x/23 = -46/23
x = -2
Now we solve for y
9x+4y=-6
9(-2) +4y = -6
-18 + 4y = -6
Add 18 to each side
-18+18 +4y = -6+18
4y = 12
Divide by 4
4y/4 = 12/4
y=3
what is the value of the expression g * (g+1)^2 for g=2
Answer:
18Step-by-step explanation:
[tex]\text{Put}\ g=2\ \text{to the expression}\ g(g+1)^2:\\\\2(2+1)^2=2(3)^2=2(9)=18[/tex]
What are the solutions of 12 – x2 = 0?
O x=273 and x = -213
O x= 3,
and x = -3/2
x = 4/5 and x = -4/3
x = 6 and x = -6
Answer:
x = ± 2[tex]\sqrt{3}[/tex]
Step-by-step explanation:
Given
12 - x² = 0 ( add x² to both sides )
12 = x² or
x² = 12 ( take the square root of both sides )
x = ±[tex]\sqrt{12}[/tex]
= ± [tex]\sqrt{4(3)}[/tex] = ± 2[tex]\sqrt{3}[/tex]
Water leaves a spigot at a rate of 462 cubic inches per minute. How many cubic feet of water is this per hour? (Round your answer to the nearest whole number.) cubic feet
Answer:
16 cubic feet per hour
Step-by-step explanation:
This is simple conversion from inches to feet.
Step 1: Write the scale of conversion
---> quantity of water in 1 minute = 462 cubic inches
--->1 cubic feet = 1728 cubic inches
--->1 hour = 60 minutes,
Step 2: Calculate feet per hour
Quantity of water in 1 hour = 0.0347 x 462
---> quantity of water in 1 hour = = 16.0314 cubic feet
---> Rounded off to--> 16 cubic feet
Therefore, 462 cubic inches per minute is 16 cubic feet of water per hour
Answer:
16 cubic feet of water
Step-by-step explanation:
Given,
Water leaves the spigot at a rate of 462 cubic inches per minute,
That is, the quantity of water in 1 minute = 462 cubic inches
1 cubic feet = 1728 cubic inches
⇒ 1 cubic inches = [tex]\frac{1}{1728}[/tex] cubic feet,
Thus, the quantity of water in 1 minute = [tex]\frac{462}{1728}[/tex] = [tex]\frac{77}{288}[/tex] cubic feet
Also, 1 hour = 60 minutes,
⇒ 1 minute = [tex]\frac{1}{60}[/tex] hours,
Hence, quantity of water in [tex]\frac{1}{60}[/tex] hour = [tex]\frac{77}{288}[/tex] cubic feet
⇒ quantity of water in 1 hour = [tex]\frac{60\times 77}{288}=\frac{4620}{288}[/tex] = 16.0416666667 cubic feet ≈ 16 cubic feet,
Hence, 16 cubic feet of water is this per hour.
Which of the following polynomials represents a difference of squares? x^2-1,x^2-8,4x^2+16,9x^2-18
Answer:
[tex]x^{2} -1[/tex]
Step-by-step explanation:
we know that
Every difference of squares problem can be factored as follows:
[tex]a^{2}-b^{2}=(a+b)(a-b)[/tex]
If the polynomial represent a difference of squares every number must be a perfect square (Remember that a number is a perfect square if its square root is an integer.)
Verify each case
case 1) we have
[tex]x^{2} -1[/tex]
In this case both numbers are perfect square
so
[tex]x^{2} -1=(x+1)(x-1)[/tex]
therefore
The polynomial represent a difference of squares
case 2) we have
[tex]x^{2} -8[/tex]
In this case 8 is not a perfect square
therefore
The polynomial not represent a difference of squares
case 3) we have
[tex]4x^{2} +16[/tex]
[tex]4x^{2}+16=4(x^{2}+4)[/tex]
In this case both numbers are perfect square
but is a sum of squares
therefore
The polynomial not represent a difference of squares
case 4) we have
[tex]9x^{2}-18[/tex]
[tex]9x^{2}-18=9(x^{2}-2)[/tex]
In this case 2 is not a perfect square
therefore
The polynomial not represent a difference of squares